2014
DOI: 10.1515/jpem-2013-0310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of insulin resistance and metabolic syndrome in a group of obese Czech children

Abstract: The relatively high incidence of insulin resistance in obese children without MS questions the prevailing diagnostic criteria of, perhaps, falsely excluding some cases of, MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The 15 primary studies included in our systematic review were all cross-sectional studies [ 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and no new articles were included after the snowballing process.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 15 primary studies included in our systematic review were all cross-sectional studies [ 13 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], and no new articles were included after the snowballing process.…”
Section: Resultsmentioning
confidence: 99%
“…The studies included reported pediatric MetS data regarding European countries; specifically, 34% ( n = 5) were conducted in Spain [ 19 , 26 , 27 , 28 , 29 ], 13% ( n = 2) in Romania [ 21 , 22 ], 13% ( n = 2) in Italy [ 13 , 24 ], 13% ( n = 2) in Poland [ 17 , 18 ], 13% ( n = 2) in Slovakia [ 23 , 25 ], 1 (7%) in Lithuania [ 18 ], and 1 (7%) in the Czech Republic [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Obesity and OW may also have an impact on the respiratory system via different mechanisms, including a direct effect of fat in the chest wall to cause structural changes and decrease the volume of the lungs, especially the expiratory reserve volume [ 34 ]. Furthermore, because adipose tissue is the largest endocrine organ in the body, when its temperature increases, progressive metabolic changes occur [ 35 ]. Endothelial dysfunction, a lower mitochondrial density, and oxygen transfer volume might also be reasons for a lower VO 2 .…”
Section: Discussionmentioning
confidence: 99%